2014
DOI: 10.1111/cpr.12149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anodic titanium dioxide nanotubes of different diameters on macrophage secretion and expression of cytokines and chemokines

Abstract: TiO2 nanotube surfaces, especially of 80 nm TiO2 nanotube, reduced inflammatory response in vitro, which might be part of a basis for rapid osseointegration in implants with TiO2 nanotube surfaces in animal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…At the micron level, blasting and etching produces a severely pitted surface and subsequent storage in saline not only results in a hydrophilic surface (modSLA), but also the spontaneous formation of nanoscale sized surface structures (Wennerberg, Svanborg, Berner, & Andersson, ). These features have been shown by our group (Alfarsi et al, ; Hamlet et al, ) and others (Hotchkiss et al, , ; Lu & Webster, ; Lü et al, ) to affect both the attachment of monocytes and macrophages, as well as the gene expression and secretion of pro‐inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 73%
“…At the micron level, blasting and etching produces a severely pitted surface and subsequent storage in saline not only results in a hydrophilic surface (modSLA), but also the spontaneous formation of nanoscale sized surface structures (Wennerberg, Svanborg, Berner, & Andersson, ). These features have been shown by our group (Alfarsi et al, ; Hamlet et al, ) and others (Hotchkiss et al, , ; Lu & Webster, ; Lü et al, ) to affect both the attachment of monocytes and macrophages, as well as the gene expression and secretion of pro‐inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 73%
“…To date, many studies have addressed the key roles of Ti implants in anti-inflammatory responses and have emphasized the important role of nanostructured surfaces. 44,[51][52][53][54] However, most of these studies have focused on the proliferation, adhesion, and secretion of pro-inflammatory cytokines from macrophages on the material. [53][54][55] Yao et al similarly used different voltages to fabricate nanotube surfaces and found that larger nanotubular surfaces (120 nm) could inhibit the expression and secretion of pro-inflammatory cytokines in macrophages.…”
mentioning
confidence: 99%
“…The cellular responses are different toward one-dimensional arrays, such as implants and scaffolds with varying morphologies and structures [140][141][142]. The morphology, including pore size (or top-side diameter) and length of the tubular TiO 2 arrays, mainly determines cell viability and proliferation through the modulation of the focal adhesion kinase and Ras homolog family member A (RhoA) pathways [35,143,144]. The macrophage inflammatory effect of tubular arrays is also controllable through the inhibition of mitogen-activated protein kinases and nuclear factor-κB pathways [145].…”
Section: In Vitro Cytotoxicity Assessmentsmentioning
confidence: 99%